Jomlo sampai Halal: Refleksi Sosiologis Budaya Generasi Milenial pada Mahasiswa Jomlo di IAIN Pontianak - Khairunnisyah Khairunnisyah; Zaenuddin Hudi Prasojo (Faculty of Social and Political Sciences - UIN Walisongo Semarang, 2019)
The article is based on the fact that “jomlo” or being single has become a new trend as a sociological phenomenon and the product of the practice of hijrah within the life of Muslim youth, especially Indonesian Muslim students. The concept of dating for those who practice the